Code Mixing in the Lyrics of the Song “You Never Know” by Blackpink - Suwiyah, Suwiyah; Kholis, Adhan (JLA (Jurnal Lingua Applicata), 2024)
This research was a study of language code mixing contained in the lyrics of a song titled “You Never Know” by Blackpink. This study aimed to identify the forms of code mixing contained in the lyrics of the song you never know by black pink, identify the types of code mixing used in the song lyrics, and describe the source language of the code mixing contained in the lyrics of the song. The method used in this study was content analysis, which was a qualitatively oriented technique, usually used to determine the character of documents or to compare them. The conclusion obtained from this study was the forms of code mixing contained in the lyrics of the song You Never Know by Blackpink consisting of inserting words, phrases and clauses. Code mixing in the form of words totaling 8 data, phrases totaling 20 data and clauses totaling 10 data. The type of code mixing used in the lyrics of the song you never know by Blackpink was alternation code mixing. The outer code mixing used was 8 data. The source language contained in the lyrics of the song You Never Know by Blackpink came from English and Korean. The code-mixed from English language was 26 data and Korean was 44 data. Through this research, it can be suggested that further researchers can be developed with the theory of code switching which is closely related to code switching.